Destined to Leave Hindustan for Suriname? - Matthijs Kraijo (Tijdschrift voor Sociale en Economische Geschiedenis, 2022)
This article investigates the post-indenture choice of Hindustani indentured labour migrants in Suriname either to settle in Suriname or repatriate to India between 1873 and 1940. Based on extensive demographic statistical analyses and the autobiography of Rahman Mohammed Khan, this research concludes that familial relations, especially those formed in Suriname, had a strong effect on the relative share of Hindustanis settling themselves in Suriname after their contract period. Additionally, this study convincingly proves that the Surinamese context had an important effect on the development of the individual life courses of Hindustanis.